Diseases affecting oil palm - Álvarez, Elizabeth (Burleigh Dodds Science Publishing Limited, 2018)
The oil palm (Elaeis guineensis Jacq.) is one of the world’s major sources of edible oil and a precursor of biodiesel fuel. This chapter reviews the oil palm diseases which act as a major production constraint in West Africa, South East Asia and South and Central America. The chapter also describes the characteristics of these key diseases and highlights the methods that are currently being applied to control them.